Yolk mass variation in White-rumped Swallows (Tachycineta leucorrhoa) - Barrionuevo, Melina (2014)
Egg mass production is costly, but hatching from heavier eggs could be beneficial for the nestling's phenotype and fitness. Egg mass could be influenced by proximate causes, like food abundance, female condition, environmental conditions, and/or by ultimate causes, such as females depositing resources differentially within a clutch to increase the biological fitness of some eggs. Yolk mass, although poorly studied, is the source of nutrients for the embryo, so its mass should be more influential for the nestlings than total egg mass. We used a technique that allowed us to measure yolk size without destroying the eggs. We studied yolk mass in 212 eggs of White-rumped Swallows (Tachycineta leucorrhoa) and found that yolk mass was influenced by laying order, with last laid eggs having heavier yolks than first laid eggs, and the pattern was consistent with egg mass variation. Food abundance also affected yolk mass: when insect availability was high the yolks were heavier. We conclude that embryos in the last laid eggs have more resources from which to develop, and excluding food abundance, neither environmental conditions nor female's condition affected yolk mass. We encourage other researchers to study yolk mass given that multiple variables affected total egg mass.